The effect of hypothetical case law in the development of the situational approach - Bychou, Omar (Journal of Educational and Psychological Sciences, 2023)
The study aims to highlight the relationship between hypothetical (estimated) case law and what is happening in current theories of action. These theories work on improving human behavior from the point of view of the situational approach and on what this jurisprudential work can contribute to the understanding and improvement of this approach as a procedural aspect of the skills approach in education and training. This forced us to research each of the foundations of hypothetical jurisprudence, and the foundations of postural work (the situational approach) from the joint launch of their work on the basis of hypothetical situations. To achieve the objectives of this study, an inductive- analytical method has been used to extrapolate the texts of the mechanism of virtual jurisprudence with regard to postural work and analysis. Additionally, a pedagogical rooting of this type of jurisprudence, in the definition of its purposes and the mechanisms of its functioning and its status are also implemented. One result of this study was that jurisprudential work approach that pragmatic education (Freire, Dewey,...), because they imagine the problem at the social level, rooted in the human environment. A number of recommendations have been made, including broadening the scope of the fields of work of educational sciences and jurisprudence in its realist and predictive dimensions because of its authentic link of transmission (transfer of the original rule to the branch) with the behavioral framework of social practices.
Keywords: Hypothetical case law; situational approach; sciences of education